Axially Extended-Volume C-Arm CT Using a Reverse Helical Trajectory in the Interventional Room - Yu, Zhicong; Maier, Andreas; Lauritsch, Günter; Vogt, Florian; Schönborn, Manfred; Köhler, Christoph; Hornegger, Joachim; Noo, Frédéric (IEEE Transactions on Medical Imaging, 2015)
UnivIS-Import:2015-03-09:Pub.2015.tech.IMMD.IMMD5.axiall

C-arm Computed Tomography with Extended Axial Field-of-View - Yu, Zhicong (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2013)
C-arm computed tomography (CT) is an innovative imaging technique in the interventional room that enables a C-arm system to generate 3D images like a CT system. Clinical reports demonstrate that this technique can help reduce treatment-related complications and may improve interventional efficacy and safety. However, currently, C-arm CT is only capable of imaging axially-short object, because it employs a single circular data acquisition geometry. This shortcoming can be a problem in some intraoperative cases when imaging a long object, e.g., the entire spine, is crucial. A new technique, C-arm CT for axially-long objects, namely extended-volume C-arm CT, has to be developed. This thesis aims at achieving this development. In particular, this thesis designs and analyzes data acquisition geometries as well as develops and implements reconstruction algorithms for extended-volume C-arm CT. The thesis consists of three parts. In the first part, we studied three data acquisition geometries and invented two thereof. For these geometries, we investigated their feasibility on a C-arm system and analyzed their possibility for efficient, theoretically-exact and -stable (TES) reconstruction algorithms. We observed that the reverse helical trajectory is a good start for real data test and the novel ellipse-line-ellipse trajectory is a good candidate for efficient TES image reconstruction. In the second part, we developed and implemented geometry-specific reconstruction algorithms. For the reverse helix, we designed three Feldkamp-Davis-Kress (FDK)-type reconstruction methods. Among the three methods, the Fusion-RFDK and Fusion-HFDK methods are preferred as they are more practical and produce acceptable images for extended-volume C-arm CT. For the ellipse-line-ellipse trajectory, we established an efficient TES reconstruction scheme, which makes proficient use of the geometry of this trajectory. In the third part, we conducted the first experiment for extended-volume C-arm CT on a laboratorial Artis zeego system. In this experiment, cone-beam data were reliably acquired using the reverse helical trajectory and 3D images were successfully reconstructed by the Fusion-RFDK method. The consistency among theoretical understanding, simulation results and achieved image quality from a real system strongly demonstrate feasibility of extended-volume C-arm CT in the interventional room.<br
UnivIS-Import:2016-07-26:Pub.2013.tech.IMMD.IMMD5.carmco
Keywords: C-arm; Computed Tomography

Efficient and Exact C-arm Cone-Beam Imaging for Axially Extended Field-of-View using the Ellipse-Line-Ellipse Trajectory - Yu, Zhicong; Lauritsch, Günter; Hornegger, Joachim; Noo, Frédéric (Proceedings of The third international conference on image formation in X-ray computed tomography, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.effici

Ellipse-line-ellipse source trajectory and its R-line coverage for long-object cone-beam imaging with a C-arm system - Yu, Zhicong; Noo, F.; Lauritsch, G.; Dennerlein, Frank; Hornegger, Joachim (Medical Imaging 2012: Physics of Medical Imaging, 2012)
Over the last decade, significant progress has been made in terms of treatment of diseases using minimallyinvasive procedures. This progress was facilitated through multiple refinements of the imaging capabilities of C-arm systems in the interventional room, and more sophisticated procedures may become feasible by further refining the performance of these systems. Our primary focus is to eliminate two strong limitations of the current circular cone-beam imaging approach: cone-beam artifacts and limited extent of the volume covered in the direction of the patient bed. To solve this problem, we seek a source trajectory that (i) is complete in terms of Tuy's condition, (ii) can be periodically-repeated without discontinuities to allow long-object imaging, (iii) is practical, and (iv) offers full R-line coverage (an R-line is a line that connects any two source positions). A trajectory that satisfies all of our constraint is the Arc-Extended-Line-Arc(AELA) trajectory. Unfortunately, this trajectory does not allow smooth, continuous scanning at reasonable dose. In this work, we propose a new data acquisition geometry: the Ellipse-Line-Ellipse (ELE) trajectory. This geometry satisfies all of our constraints along with the attractive feature that smooth, continuous scanning at reasonable dose is enabled. © 2012 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).

Extended Volume Image Reconstruction Using the Ellipse-Line-Ellipse Trajectory for a C-arm System - Yu, Zhicong; Noo, Frédéric; Lauritsch, Günter; Hornegger, Joachim (Proceedings of The 12th International Meeting on Fully Three-Dimensional Image Reconstruction in Radiology and Nuclear Medicine, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD5.extend

FDK-type reconstruction algorithms for the reverse helical trajectory - Yu, Zhicong; Noo, Frédéric; Dennerlein, Frank; Lauritsch, Günter; Hornegger, Joachim (2011 IEEE Nuclear Science Symposium and Medical Imaging Conference, NSS/MIC 2011, 2012)
For emergency cases in the interventional room, 3D long-object cone-beam(CB) imaging using a C-arm system could save valuable time and reduce risks to the patient by avoiding the traditionally-used CT scan, and thus could potentially be a crucial tool for patient health. To accomplish such a task, the reverse helix is an attractive trajectory, however theoretically-exact and stable (TES) reconstruction with a reverse helix is challenging. Two TES solutions are available, but both of them come with a heavy computational load and some issues in terms of image quality. This work proposes three new approximate reconstruction algorithms for the reverse helix that are stable and efficient, and thus practical. Though not exact, reconstruction results obtained from all three methods appear acceptable. © 2011 IEEE.

Frist experimental results on long-object imaging using a reverse helical trajectory with a C-arm system - Yu, Zhicong; Maier, Andreas; Schönborn, Manfred; Vogt, Florian; Köhler, Christoph; Lauritsch, Günter; Hornegger, Joachim; Noo, Frédéric (Proceedings of The second international conference on image formation in x-ray computed tomography, 2012)

Simulation tools for two-dimensional experiments in x-ray computed tomography using the FORBILD head phantom - Yu, Zhicong; Noo, Frédéric; Dennerlein, Frank; Wunderlich, Adam; Lauritsch, Günter; Hornegger, Joachim (Physics in Medicine and Biology, 2012)
Mathematical phantoms are essential for the development and early stage evaluation of image reconstruction algorithms in x-ray computed tomography (CT). This note offers tools for computer simulations using a two-dimensional (2D) phantom that models the central axial slice through the FORBILD head phantom. Introduced in 1999, in response to a need for a more robust test, the FORBILD head phantom is now seen by many as the gold standard. However, the simple SheppLogan phantom is still heavily used by researchers working on 2D image reconstruction. Universal acceptance of the FORBILD head phantom may have been prevented by its significantly higher complexity: software that allows computer simulations with the SheppLogan phantom is not readily applicable to the FORBILD head phantom. The tools offered here address this problem. They are designed for use with Matlab®, as well as open-source variants, such as FreeMat and Octave, which are all widely used in both academia and industry. To get started, the interested user can simply copy and paste the codes from this PDF document into Matlab® M-files. © 2012 Institute of Physics and Engineering in Medicine.

X-ray source trajectories and their R-line coverage for long-object CB imaging with a C-arm system - Yu, Zhicong; Noo, Frédéric; Dennerlein, Frank; Lauritsch, Günter; Hornegger, Joachim (The first international conference on image formation in x-ray computed tomography, 2010)